A STUDY OF SERUM URIC ACID IN DIABETES MELLITUS AND PREDIABETES IN A SOUTH INDIAN TERTIARY CARE HOSPITAL - M., Sudhindra Rao; Sahayo, Bino John (Journal of Health and Allied Sciences NU, 2012)
Background: Several epidemiologic studies have reported that high serum levels of uric acid are strongly associated with prevalent health conditions such as obesity, insulin resistance, metabolic syndrome, essential hypertension and renal disease. This study aimed to investigate the level of serum uric acid in Type 2 diabetes mellitus, pre-diabetics and non diabetics (controls) in south Indian population.Methods: Uric acid level was measured by Uricase-PAP methodology in patients with Diabetes (n=71)/Pre diabetes (n=12)/ Control groups (n=34). Using ANOVA test, uric acid levels in the above three groups were compared based on age, sex and other factors which can affect uric acid level.Results: The mean serum uric acid level was lower in control group (3.84mg/dl), rose in pre-diabetics (4.88mg/dl) and again decreased in diabetics (3.78mg/dl). P value comparing control and pre-diabetes was 0.009, p-value comparing pre-diabetes and diabetes was 0.003 and p-value comparing control and diabetes was 0.982 (p value <0.05 being significant).Conclusion: The serum uric acid level being higher in pre-diabetes than controls and lower in diabetes mellitus than pre-diabetes may serve as a potential inexpensive biomarker of deterioration of glucose metabolism.
Keywords: Serum uric acid; Diabetes mellitus; Pre-diabetes